Effects of FACE on denitrification activity in paddy-field soil - WANG Shu-yi; HAN Lin; SHI Yi; MEI Bao-lin; ZHU Jian-guo (浙江大学学报. 农业与生命科学版)
A free-air CO2 enrichment (FACE) experiment was used to investigate the effects of elevated atmospheric CO2 concentration on soil denitrification activities. The FACE system was conducted under a rice/wheat rotation at Jiangdu, China. The numbers of denitrifying bacteria, the activities of nitrate reductase and nitrite reductase was studied by sampling fresh soils from the fields with two different N fertilization levels (Usual N and Low N) and two rice straw incorporation levels [HR (half straw return) and NR (no straw return)] exposed to the elevated and ambient CO2 during the rice-growing season in 2005. And the denitrification potential was determined at jointing stage. The results showed that elevated atmospheric CO2 concentrations decreased denitrifying bacteria numbers, especially at UN and NR conditions (P<0.01). FACE had little impact on the activities of nitrate reductase and nitrite reductase. The study on DP (denitrification potential) showed that DP from FACE plots only arrived to 84.21% and 97.46% of ambients under LN and UN levels. The denitrification was restraind because of their competition between plant growing and microbial activity promoted by FACE.